Development of child-friendly interior design at Tumbuh Kembang Daycare, Sinduharjo, Yogyakarta - Rahmaris, Nastiti Ilma; Ambarwati, Dwi Retno Sri (Universitas Negeri Yogyakarta, 2024)
This study aims to design the interior of a child-friendly daycare by considering functional, comfort, safety and aesthetic aspects. Research and Development (R&D) is the method used in this study. The results of this study are the development of a child-friendly interior at the Sinduharjo Yogyakarta Growth and Development Daycare, which produces 2-dimensional and 3-dimensional images and presentation videos. The study provides the following results: 1) Child-friendly interior design with natural nuance literacy and considering safety, comfort, functional and aesthetic aspects, 2) Optimization of the function of each existing space by utilising space and converting space, 3) Application of furniture that is safe for children and multifunctional, 4) Creation of branding for daycare by creating a cheerful and child-friendly atmosphere, 5) Processing of elements that form a space such as the floor, walls and ceiling to be more child-friendly and in accordance with the natural literacy atmosphere. Overall, the design considers essential aspects of interior design, important aspects of children's space, use of colour, spatial layout, criteria for facilities and infrastructure, space requirements, and child therapy rooms.